Guidelines for development of self-management to enhance career characteristics of junior high school students - Prasertsin, Ujsara; Srihaset, Kamontip; Loanoi, Areerat (Kasetsart Journal of Social Sciences, 2023)
The objectives of this research were: (1) to assess needs for self-management; (2) to develop career characteristics scales; and (3) to explore self-management guidelines to enhance the career characteristics of junior high school students. Mixed-method research was designed for this study. The sample group for quantitative research consisted of 1000 junior high school students in Bangkok and its vicinity and 9 experts participating in in-depth interviews for qualitative research. The research results were as follows: (1) The results of the needs assessment for self-management of junior high school students revealed that Component 1, Awareness, had the highest need (PNImodified = 0.182); (2)The Cronbach alpha coefficients for each component of the self-management measurement of junior high school students were .886, .875, .810, .796, .787 and .692, respectively. The results of coherence testing of the model revealed that the structural validity of the measurement model for career characteristics of junior high school students was consistent and harmonious with the empirical data determined by NFI = .900, IFI = .920, TLI = .915, RMR = .047, RMSEA = .058 and CFI = .920. The harmonization index was in accordance with the criteria; and (3) The self-management to enhance career characteristics of junior high school students included 5 guidelines: (1) organizing activities to enhance learning from real-life situations; (2) using media or information technology in the enhancement; (3) using self-assessment tests; (4) practicing self-learning experiences fostering essential skills; and (5) counseling and guidance processes of self-management to enhance career characteristics.